2018
DOI: 10.1186/s13068-017-1002-y
|View full text |Cite
|
Sign up to set email alerts
|

Working towards recalcitrance mechanisms: increased xylan and homogalacturonan production by overexpression of GAlactUronosylTransferase12 (GAUT12) causes increased recalcitrance and decreased growth in Populus

Abstract: BackgroundThe development of fast-growing hardwood trees as a source of lignocellulosic biomass for biofuel and biomaterial production requires a thorough understanding of the plant cell wall structure and function that underlie the inherent recalcitrance properties of woody biomass. Downregulation of GAUT12.1 in Populus deltoides was recently reported to result in improved biomass saccharification, plant growth, and biomass yield. To further understand GAUT12.1 function in biomass recalcitrance and plant grow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
34
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 51 publications
5
34
0
Order By: Relevance
“…Another gene with a similar function, Potri.004G111000 (GAUT9) was detected for the same multitrait GWAS from the Corvallis common garden (Chhetri et al, 2019). GAUT8 and GAUT9 belonged to the same clade B1 in a phylogenetic tree based on the GAUT protein family of Arabidopsis thaliana and P. trichocarpa (Biswal et al, 2018). GAUT9 affects leaf size in Populus deltoides (Chhetri et al, 2019) whereas GAUT8 (also known as QUASIMODO1) has high expression in stems in Arabidopsis (Caffall et al, 2009) and is thought to be involved in cell wall pectic homogalacturonan (HG) and xylan biosynthesis (Orfila et al, 2005;Verger et al, 2016).…”
Section: Multitrait Gwas Genesmentioning
confidence: 87%
“…Another gene with a similar function, Potri.004G111000 (GAUT9) was detected for the same multitrait GWAS from the Corvallis common garden (Chhetri et al, 2019). GAUT8 and GAUT9 belonged to the same clade B1 in a phylogenetic tree based on the GAUT protein family of Arabidopsis thaliana and P. trichocarpa (Biswal et al, 2018). GAUT9 affects leaf size in Populus deltoides (Chhetri et al, 2019) whereas GAUT8 (also known as QUASIMODO1) has high expression in stems in Arabidopsis (Caffall et al, 2009) and is thought to be involved in cell wall pectic homogalacturonan (HG) and xylan biosynthesis (Orfila et al, 2005;Verger et al, 2016).…”
Section: Multitrait Gwas Genesmentioning
confidence: 87%
“…Our results are consistent with previous findings that pectin, although present in low abundance in woody tissues, contributes to biomass recalcitrance, as down‐regulation of pectin synthesis enhanced sugar yield in saccharification assays (Biswal et al , ; Biswal et al , ), and over‐expression of GAUT12 to increase HG content decreased saccharification yield (Biswal et al , ). Deletion of a gene cluster encoding a suite of pectolytic enzymes of Caldicellulosiruptor bescii reduced sugar yields in saccharification assays (Chung et al , ), whereas controlled expression of recombinant pectinases enhanced digestibility of A. thaliana (Tomassetti et al , ).…”
Section: Discussionmentioning
confidence: 99%
“…However, genetic modification of enzymes involved in biosynthesis of the xylan backbone results in decreased stem strength (Brown et al, 2007;Brown et al, 2005;Persson et al, 2007). Over-expression of GALACTURONOSYL TRANSFERASE 12 (GAUT12) increased recalcitrance to enzymatic digestion but also resulted in decreased growth in Populus (Biswal et al, 2018a). Although presumed to be involved in HG backbone synthesis, knockdown of GAUT12 results in reduced xylan content and in increased growth (Biswal et al, 2015).…”
Section: Expression Of Rg-lyase Facilitates Cell-cell Separationmentioning
confidence: 99%
“…Other GAUT genes have also been shown to affect cell wall properties and leaf size in Populus. Downregulation of a GAUT12 homolog in P. deltoides showed decreased xylan and pectin content in the cell wall and increased biomass yield (Biswal et al, 2015), while overexpression showed a reduction in overall plant productivity and resulted in smaller leaves, reduced xylem cell numbers and size, and an increase in the amount of xylose and galacturonic acid in the cell wall (Biswal et al, 2018b). Downregulation of GAUT4 in P. deltoides resulted in decreased pectic homogalacturonan and rhamnogalacturonan II and increased plant height, diameter, leaf area, and biomass (Biswal et al, 2018a).…”
Section: New Phytologistmentioning
confidence: 99%